Comprehensive effect of the mechanical properties, laminated structure and healing conditions on the self-healing behaviors of laminated Al2O3-MgO ceramic composites. Issue 10 (July 2019) - Sun, Junlong; Liu, Changxia; Zhang, Rui; Gong, Feng; Wang, Chao; Li, Gang
Abstract: The comprehensive effect of the mechanical properties, laminated structure and healing conditions on the self-healing behaviors of laminated Al2 O3 -MgO ceramic composites was researched. The flexural strengths before and after healing at the temperatures of 715, 815 and 915 °C for 30 min, 60 min and 90 min were measured. According to recovering rate the best healing condition was 900 °C for 60 min. The crack-healing ability of the laminated Al2 O3 -MgO ceramic composites was improved due to the enhancement of the original flexural residual effect and the oxide content effect by the elimination of pores and the filling of cracks. In addition, the factors influencing the original flexural residual effect and the oxide content effect were analyzed. Meanwhile, the effects of the particle size and the healing temperature on the healing ability were analyzed qualitatively based on the healing of a single particle model.